The Influence Of Compensation And Work Discipline On Employee Performance At PT. Sicepat Ekspres Indonesia Bintaro Branch Tangerang Selatan - Banjal, Teul Panda; Haris, Ruli (Transforma Jurnal Manajemen, 2024)
This research aims to determine the effect of compensation and work discipline on employee performance at PT Sicepat Ekspres Indonesia Bintaro Branch, South Tangerang. The method used is explanatory research with analytical techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this research are that compensation has a significant effect on employee performance by 57.2%. Hypothesis testing shows that t count > t table or (8.962 > 2.000). Work discipline has a significant effect on employee performance by 43.2%, hypothesis testing obtained t count > t table or (6,752 > 2,000). Compensation and work discipline simultaneously have a significant effect on employee performance with the regression equation Y = 9.015 + 0.471X1 + 0.322X2 and an influence contribution of 0.685, the hypothesis test obtained calculated F > F table or (64.022 > 2.760).